What policies for greening the crisis response and economic recovery? Lessons learned from past green stimulus measures and implications for the COVID-19 crisis - Agrawala, Shardul (OECD Publishing, 2020)
This paper evaluates green stimulus packages that were introduced in response to the global financial crisis (GFC) of 2007-08 and draws lessons relevant for greening the recovery from the Coronavirus (COVID-19) crisis. The paper underscores the importance of building in policy evaluation mechanisms into green stimulus measures. It also provides evidence that the implementation of sufficiently large, timely and properly designed green stimulus measures can generate economic growth, create jobs and bring about environmental benefits. However, there are also trade-offs between competing economic, environmental and social policy objectives, which underscores the importance of proper policy design
Keywords: Environment; Finance and Investment; Economics